Growth Behaviour of Two-centuries Old Crop Deodar (Cedrus deodara Loudon) - Dabral, S. N.; Singh, M. M. (Indian Forester, 1966)
The analysis of crop data from two-century old active sample plots for Cedrus deodara laid out in 1932 when the crop was 165 years old is given in this note. The results are interesting in so far as there is no conspicuous dectine in growth rate even at the advancing age. Perhaps a question may arise if the rotation period for the species in such localities could be raised but full consideration has to be given, inter alia, to the quality of timber produced at this age and the logging damages to natural regeneration usually met with on exploitation of such large trees.